Reading Others / Reading Texts: The Hermeneutics of Suspicion in Brief Interviews with Hideous Men. Issue 5 (19th October 2020) - Prout, Matt
ABSTRACT: David Foster Wallace's famous discussion of postmodern irony can be seen to share much with the recent reappraisal of the mode of postmodern thinking known as "critique" in books such as Rita Felski's The Limits of Critique (2015). Wallace's collection Brief Interviews with Hideous Men (1999) can be read as interrogating "the hermeneutics of suspicion" (the central reading strategy of critique) through its presentation of characters who are attached to this mode of thinking. Although this collection offers a clear warning against the dangers of a hermeneutics of suspicion, this warning is complicated by the fact that, as a text, it requires – and calls on – our suspicion in order to be understood. At a time when Wallace's own work is increasingly the subject of critique, turning to this collection, and its interrogation of suspicion, can provide us with a place for thinking about the kinds of suspicion we ought to bring to our reading of Wallace. By both illustrating the dangers of suspicious reading practices, and demanding such practices in order to be read, the collection forces readers to think about their own role in deciding when to exercise and when to withhold their suspicion.